Ответ:
Объяснение:
1)5х=6,5
х=6,5/5
х=(65/10)/5
х=(65/10)*(1/5)
х=13/10
х=1,3
2)2х+3=х-4
2х-х=-3-4
х=-7
3)5х+6=3х-8
5х-3х=-8-6
2х=-14
х=-14/2
4)2(2х+1)=6-х
4х+2=6-х
4х+х=6-2
5х=4
х=4/5
5)2(х-1)=3(х+1)
2х-2=3х+3
2х-3х=3+2
-х=5
х=-5
6)2х-7=4х+5
2х-4х=5+7
-2х=12
х=12/(-2)
х=-6
7)6х+4=4х-7
6х-4х=-7-4
2х=-11
х=-11/2
х=-5,5
8)8х-10=5х+2
8х-5х=10+2
3х=12
х=12/3
х=4
1. 5x=6.5
x=6.5/5=1.3
2. 2x+3=x-4
2x-x=-4-3
x=-7
3. 5x+6=3x-8
5x-3x=-8-6
2x=-14
4. 2(2x+1)=6-x
4x+2=6-x
4x+x=6-2
5x=4
x=4/5=0.8
5. 2(x-1)=3(x+1)
2x-2=3x+3
2x-3x=3+2
-x=5
x=-5
6. 2x-7=4x+5
2x-4x=5+7
-2x=12
x=-6
7. 6x+4=4x-7
6x-4x=-7-4
2x=-11
x=-11:2=-5.5
8. 8x-10=5x+2
8x-5x=2+10
3x=12
x=4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
1)5х=6,5
х=6,5/5
х=(65/10)/5
х=(65/10)*(1/5)
х=13/10
х=1,3
2)2х+3=х-4
2х-х=-3-4
х=-7
3)5х+6=3х-8
5х-3х=-8-6
2х=-14
х=-14/2
х=-7
4)2(2х+1)=6-х
4х+2=6-х
4х+х=6-2
5х=4
х=4/5
5)2(х-1)=3(х+1)
2х-2=3х+3
2х-3х=3+2
-х=5
х=-5
6)2х-7=4х+5
2х-4х=5+7
-2х=12
х=12/(-2)
х=-6
7)6х+4=4х-7
6х-4х=-7-4
2х=-11
х=-11/2
х=-5,5
8)8х-10=5х+2
8х-5х=10+2
3х=12
х=12/3
х=4
Ответ:
1. 5x=6.5
x=6.5/5=1.3
2. 2x+3=x-4
2x-x=-4-3
x=-7
3. 5x+6=3x-8
5x-3x=-8-6
2x=-14
x=-7
4. 2(2x+1)=6-x
4x+2=6-x
4x+x=6-2
5x=4
x=4/5=0.8
5. 2(x-1)=3(x+1)
2x-2=3x+3
2x-3x=3+2
-x=5
x=-5
6. 2x-7=4x+5
2x-4x=5+7
-2x=12
x=-6
7. 6x+4=4x-7
6x-4x=-7-4
2x=-11
x=-11:2=-5.5
8. 8x-10=5x+2
8x-5x=2+10
3x=12
x=4